HEMODYNAMIC AND STRUCTURAL ALTERATIONS OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH MORBID OBESITY: A LITERATURE REVIEW (CIPEEX, 2025)
Introduction: Obesity, defined as a Body Mass Index (BMI) equal to or greater than 30, is a critical factor for cardiovascular health, manifesting itself in three distinct degrees. Objective: The objective of this review was to explore the cardiovascular changes associated with obesity and their implications for health. Method: Using databases such as PubMed and the Virtual Health Library (BVS), articles published between 2019 and 2024 were selected, focusing on "cardiovascular disease," "obesity," and "hemodynamics." The method involved filtering relevant studies, resulting in 11 articles addressing relevant issues regarding the cardiovascular effects of obesity. Results: The results showed that obesity induces significant hemodynamic changes, such as left ventricular remodeling and right ventricular dysfunction, and contributes to chronic inflammation and cardiac fibrosis. It was also observed that, paradoxically, individuals with moderate obesity may have a better cardiovascular prognosis compared to normal-weight individuals with heart failure. Conclusion: In conclusion, a multifaceted approach to the treatment of obesity, including lifestyle changes, pharmacological therapies, and bariatric surgery, may potentially reverse or mitigate the adverse cardiovascular changes associated with this condition.
Keywords: obesity; cardiovascular disease; hemodynamics